The influence of university supports on entrepreneurial competencies among students in Universiti Teknologi Mara (UiTM) Melaka, City Campus / Muhammad Aminuddin Badli - Badli, Muhammad Aminuddin (Faculty of Business and Management, 2016)
The title of this research is “The Influence of University Supports on Entrepreneurial Competencies among Students in Universiti Teknologi MARA (UiTM) Melaka, City Campus”. First objectives of this research is to identify the level of entrepreneurial competencies of the students. The next objective is to study the relationship between university supports and entrepreneurial competencies among students in Universiti Teknologi MARA (UiTM) Melaka, City Campus. Four independent variables is identified, that influenced entrepreneurial competencies, which are Training Programs, Courses, Financials, and Co-curricular Activities. In order to complete the research, four hypothesis is constructed, focused on the determining the influence of the independent variables towards dependent variables. A total of 240 students have participated, from 616 total of final year students, using proportionate stratified random sampling. The researcher use primary data collection method, by questionnaire to collect data. All of the data obtained is analysed using with normality test, reliability test, frequency testing, descriptive statistical test, Pearson Correlation coefficient, and regression testing. For correlation, all variables are significant, and have fair relationship strength towards entrepreneurial competencies. For multiple regression analysis, only Training Programs, and Co-curricular activities influence entrepreneurial competencies and it can be conclude that hypothesis 1 and 4 is supported, while other variables, which are Courses and Financials does not influence entrepreneurial competencies, thus hypothesis 2 and 3 is rejected.